Work Motivation, Work Discipline, and Employee Loyalty in a Public Water Utility: The Mediating Role of Job Satisfaction - Defri Yuslana Karim; Fahrezzi Tegar Pamungkas; Muhammad Faraz Al Fath; Febrianty Febrianty; Reza Hardian Pratama (International Journal of Business, Law, and Education, 2026)
Purpose: This study examines how work motivation and work discipline influence employee loyalty in the Regional Public Drinking Water Company (PDAM) of Bandar Lampung City, with job satisfaction positioned as a mediating mechanism. Design/methodology/approach: A quantitative explanatory design was applied. Primary data were collected through a structured questionnaire administered to 82 permanent employees who had worked for at least one year. The model was assessed using partial least squares structural equation modeling (PLS-SEM). Measurement quality was evaluated through indicator loadings, average variance extracted, and composite reliability, while the structural model was evaluated using path coefficients, t-statistics, p-values, and coefficients of determination. Findings: Work discipline had the strongest positive effect on job satisfaction (β = 0.614, p < .001), followed by work motivation (β = 0.322, p = .006). Job satisfaction significantly predicted employee loyalty (β = 0.517, p < .001). Work motivation also had a direct positive effect on employee loyalty (β = 0.309, p = .003), whereas work discipline did not directly predict employee loyalty (β = 0.142, p = .273). The coefficient pattern indicates that job satisfaction is a central mechanism linking motivation and discipline to loyalty. Originality/value: The study contributes to public-sector human resource management by showing that employee loyalty in a municipal water utility depends not only on rule compliance and motivation, but also on whether these conditions translate into felt job satisfaction.